Nutritional imbalances among university students and the urgent need for educational and nutritional interventions - Torres, Keila; Cáceres-Durán, Miguel A.; Orellana, Constanza; Osorio, Martina; Simón, Layla (Frontiers in Nutrition, 2025)
IntroductionThe dietary habits of children and adolescents in Chile have been identified as inadequate, potentially contributing to low levels of essential vitamins and minerals, as well as the development of chronic diseases such as obesity and diabetes. However, the nutritional profile of Chilean university students and the impact of their diets on this profile remain largely unknown. This study aimed to assess the nutritional profile of Finis Terrae University students in the Santiago Metropolitan Region, Chile.MethodsA retrospective 24-h dietary survey, using the Automated Self-Administered 24-Hour Dietary Assessment Tool (ASA24®), was administered to 124 students between September and October 2024. Data on macronutrient and micronutrient consumption was analyzed using GraphPad Prism.ResultsAmong those surveyed, 90% reported consuming at least three meals daily (breakfast, lunch, and dinner). However, 61% consumed fewer calories than recommended, only 7% met the daily intake goals for dairy, 11% met the recommended fruit and vegetable intake, and 16% fiber intake. In contrast, 65% exceeded the upper recommended limits for sodium intake. Significant deficiencies were observed in the intake of calcium, magnesium, potassium, and vitamins A, C, D, and E. Meanwhile, the intake of copper, phosphorus, selenium, folate, niacin, riboflavin, thiamine, vitamin B6, and vitamin B12 met the recommended dietary allowances.DiscussionAlthough most of the students consumed three meals daily, the quality of their nutritional intake was suboptimal. These findings highlight the need for educational and nutritional programs to promote healthier eating habits and improve the quality of life of university students, emphasizing regular, balanced meals, developing skills in meal preparation to reduce reliance on ultra-processed foods, and prioritizing hydration with water.